Integrating Artificial Intelligence (AI) in English Learning at Higher Education - Hartono Rahim; Muhammad Basri Jafar; A. Muliati (International Journal of Language, Education, and Literature, 2025)
This study investigates the integration, perceptions, and impact of artificial intelligence (AI) in English language learning among students at the tertiary level. Using a qualitative descriptive design, data were collected through semi-structured interviews with four students representing different levels of AI engagement. Thematic analysis revealed three major findings. First, AI was primarily integrated as a complementary tool for technical assistance, such as grammar checking and idea generation. Second, students expressed positive attitudes toward AI, emphasizing its usefulness in enhancing writing skills and boosting confidence. However, concerns about ethical issues and the risk of overreliance were also identified. Third, AI positively influenced students’ learning behaviors by promoting self-regulated learning and motivation, although challenges such as technical inaccuracies and shifting social dynamics were noted. The study concludes that while AI offers valuable support in language learning, it should be used critically and responsibly. Future research is recommended to involve broader participant groups and investigate educators’ perspectives on AI integration in education..